Law, land reform and responsibilisation: A perspective from Malawi's land question - Chikosa M Silungwe (Pretoria University Law Press (PULP), 2015)
About the publication The book is a critical, genealogical analysis of land questions in the South through an original analysis of the Malawi experience. Through the author's experience in land reform and subsequent advanced research in the area, the book notes that land reform discourse is dominated by an ethos based on market as value which, in turn, has cemented the ubiquity of a universal, automatic transition from land reform to land law reform in tackling a land question in a country. Using a Foucauldian-based theory of governmentality and responsibilisation, the book provides a reassessment of the norms in land reform discourse and argues for the conception of a right to property in land as a social relation. The book reveals the parochial interests of global capital, local elites and even the land-deprived that underpin a land question. The lack of synergy between law and policy leads to the consistent emergence of two 'beings': first, a responsibilised citizen in the mould of the land deprived who constitutes a source of cheap, wage labour for the large estate agriculture sector; and second, a land owner as the efficient producer at the centre of the large estate agriculture sector. The book then proposes an alternative norm in land reform discourse based on a responsibilised State. About the editor: Chikosa M Silungwe PhD Attorney; Consultant; Academic. Table of Contents Acknowledgments Dedication Introduction 1 The context 2 Rationale and main argument 3 Market as value and land reform modelling 3.1 Market as value 3.2 Power dimension of land reform 3.3 Market-based land reform models 3.4 Reflection on market-based land reform modelling 4 On responsibilisation 5 On method 6 Final word Governmentality, responsibilisation and the land question 1 Thinking theory 2 The Foucauldian 'idea' of governmentality 2.1 Governmentality and analytics of power 2.2 Governmentality and law 3 'Everyday struggles': Conduct and counter-conduct 4 Responsibilisation: A framework for analysis 4.1 The nature of hegemonic responsibilisation 4.2 The nature people-generated responsibilisation 5 Governmentality-responsibilisation: Whither the resolution of land question in Malawi? 6 Final word 'Right', 'property' and the 'customary' space: Conceptual issues and the land question 1 The nature of the right to property 1.1 Character of a 'right' 1.2 The meaning of 'property': The right to property as a social relation 2 The right to property in land: An analysis of the 'customary' space 2.1 The root of the 'customary' space 2.2 The nature of 'customary' (land) tenure 3 The beneficial interest in land: 'Customary land' under the Malawian Land Act 4 Final word Global-local policy linkage, responsibilisation and the land question 1 Global-local policy linkage 1.1 The World Bank's land policy framework, 2003 1.2 The national macroeconomic framework as a site of conformity 2 National policy interventions in the land question 2.1 'Let sleeping dogs lie': The Presidential Commission of Inquiry on Land Policy Reform, 1996 2.2 The land utilisation studies, 1995-1998 2.3 The National Land Policy 2.4 Intervention of the Malawi Law Commission 2.5 The Green Belt Initiative 3 Final word A multiverse of interests and the land question 1 The state and the Achikumbe 2 The state and the land deprived 3 The Achikumbe and the land deprived 4 The intra-'community' dynamics 4.1 The role of chiefs 4.2 Eni malo and obwera: The 'internecine' conflict of the land deprived 5 The nature of the multiverse 6 Final word Last word: Towards a responsibilised state 1 Reiterations 2 The nature of people-generated responsibilisation: The basis of the responsibilised state 2.1 Public trust and social trust: The constitutional basis of people-generated responsibilisation 2.2 Counter-conduct and the beneficial interest in land 2.3 The land question in the political economy 3 The responsibilised state: A restatement 4 Final word 4.1 The presumptions 4.2 The wider angle 5 The thesis: a précis Bibliography